Visualizing and Quantifying the Effect of the Inhibition of HSP70 on Breast Cancer Cells Based on Laser Scanning Microscopy. (31st August 2018) - Yu, Biying; Yang, Hongqin; Zhang, Xiaoman; Li, Hui
Heat shock protein 70 has been recognized as a target for anticancer therapy. The overexpression of heat shock protein 70 is observed frequently in several types of tumors, including breast cancer. It is involved with increased cell proliferation, poor prognosis, and drug resistance in breast cancer. VER-155008 is an effective inhibitor of heat shock protein 70 that targets the adenosine triphosphatase–binding domain of heat shock protein 70. In this study, the effects of VER-155008, heat shock (43°C, 1 hour), and the combination treatment of VER-155008 and heat shock on the mitochondria of the MCF-7 breast cancer cells were investigated through a laser scanning microscope combined with mitochondrial membrane potential fluorescence probe. We observed broken mitochondria networks, decreased mitochondrial membrane potential, and cell size. The mitochondrial contents were reduced with the VER-155008 treatment and the combination treatment of VER-155008 and heat shock. The effects of the inhibition presented treatment time dependence. Moreover, the effect of the inhibition of the sole VER-155008 was alleviated when it was combined with heat shock although there was no obvious change with the sole heat shock treatment. The results indicated that VER-155008, the inhibitor of heat shock protein 70, induced apoptosis in MCF-7 breast cancer cells whatever it was in the sole or the combined manner, and its promoting apoptosis effect could be alleviated by heat shock. Our findings demonstrated that HSP70 can be a good target for developing breast cancer therapy.